Mechanisms of dust emissions from lakes during different drying stages in a semi-arid grassland in northern China - Qi, Shuai; Ren, Xiaomeng; Dang, Xiaohong; Meng, Zhongju (Frontiers in Environmental Science, 2023)
Semi-arid playas are important to grassland ecosystem species as an important source of global dust emissions. However, there is a lack of data on dust emissions during the different drying stages of grassland playas. In this study, we initially conducted the field experiments on two types of surfaces (intermittently dried and permanently dried) in playas located in semi-arid regions in northern China, and we measured dust emissions at five wind speeds in spring when wind erosion was frequent. The results showed that the intermittently dried surfaces were more prone to wind erosion, which was primarily due to the formation of a loose and fragile salt crust on the surface. In addition, the proportion of salt in the dust was higher than that for the permanently dried surfaces. Nevertheless, the total horizontal dust flux (1.13–2.3 g/cm2·min) from the intermittently dried surface was only 5%–15% that of the permanently dried surface (7.47–42.86 g/cm2·min). The dust content varied linearly with the height of the intermittently dried surface, and varied exponentially with the height of the permanently dried surface. The particles collected on the intermittently dried surface were larger (< 63 μm) than those collected on the permanently dried surface (< 10 μm), and the unit mass concentration of each ion (mainly Na+, Cl-, and SO42-) in the salt dust was also higher for the intermittently dried surface than for the permanently dried surface. Although salt dust was continuously released from the intermittently dried surface, the total amount released each time was limited. These results indicate that to attenuate the damage of salt dust storms, priority should be given to protecting permanently dried surfaces and reducing the supply of salt dust particles at the surface.